A(b-2)=c(b+3)

Simple and best practice solution for A(b-2)=c(b+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A(b-2)=c(b+3) equation:


Simplifying
A(b + -2) = c(b + 3)

Reorder the terms:
A(-2 + b) = c(b + 3)
(-2 * A + b * A) = c(b + 3)
(-2A + bA) = c(b + 3)

Reorder the terms:
-2A + bA = c(3 + b)
-2A + bA = (3 * c + b * c)

Reorder the terms:
-2A + bA = (bc + 3c)
-2A + bA = (bc + 3c)

Solving
-2A + bA = bc + 3c

Solving for variable 'A'.

Move all terms containing A to the left, all other terms to the right.

Reorder the terms:
-2A + bA + -1bc + -3c = bc + -1bc + 3c + -3c

Combine like terms: bc + -1bc = 0
-2A + bA + -1bc + -3c = 0 + 3c + -3c
-2A + bA + -1bc + -3c = 3c + -3c

Combine like terms: 3c + -3c = 0
-2A + bA + -1bc + -3c = 0

The solution to this equation could not be determined.

See similar equations:

| 6(x+5)=-12 | | 5(x-2)-3(x+1)=0 | | 6x-3=6x+2 | | 100-10x=40 | | x^2-10xy-24y^2=0 | | 9(x-5)-5(x-2)+2x= | | 2y=8-(y-2) | | 5(x+1)=12-x | | 18x+72=21 | | N+7=4 | | 9x+7x=69+x | | 5x-1=3x+115 | | 2x+38=4x+12 | | 12x+30=6x+108 | | X-4(x+3)=2 | | -2(5)+5= | | 35x=25x+1500 | | x=100+1y | | 4x^2-23x+8=-2+3 | | 5x-13+7x+3=180 | | 3(9+4)-7= | | 7x-10y=1 | | 6(x+4)=2(x+24) | | 7*5+xb=25+7x-5b | | 5x-7=58-8x | | (3x-4)/(2x-3)=(x-16)/(x-9) | | 3(x-2)=34-5x | | 7*5+ab=25+7a | | 2n-20=10 | | x^2+4x+84=0 | | 8(x+3)=2(x-36) | | 20-2n=10 |

Equations solver categories